Pregnancy in Kidney and Liver Transplant Recipients: Maternal and Fetal Risks and Management Challenges - narrative review - Napieraj, Filip; Herc, Bartosz Przemysław; Tesla, Małgorzata; Gąska, Anna Agnieszka; Gutkowska, Marta; Jabłońska, Joanna; Wasik, Joanna; Armuła, Marta; Bongage, Claire; Piechowiak, Arkadiusz (Quality in Sport, 2026)
Background. The rising success of SOT among younger pacients has made pregnancy an increasingly viable reality. However, these cases remain inherently high-risk, requiring a delicate clinical balance between maintaining graft stability, ensuring maternal safety, and supporting fetal development. Aim. This review synthesizes current evidence regarding pregnancy management and outcomes in kidney and liver transplant recipients, focusing on clinical strategies to optimize maternal and neonatal health. Material and methods. A systematic search was conducted across PubMed, Scopus, and Google Scholar. The analysis included randomized trials, systematic reviews, and clinical guidelines published in English, with a focus on high-quality, recent evidence. Results. SOT typically restores fertility within 6–12 months post-transplant, yet pregnancies in this cohort are frequently complicated. Maternal risks are dominated by hypertensive disorders, which occur at significantly higher rates than in the general population. Fetal outcomes are primarily impacted by preterm birth, leading to higher incidences of low birth weight and intrauterine growth restriction. Success hinges on a multidisciplinary approach and the strict optimization of immunosuppression. Current protocols emphasize the mandatory transition from teratogens to safer alternatives, such as Tacrolimus. However, altered pharmacokinetics during pregnancy necessitate proactive serum monitoring and dosage adjustments to compensate for accelerated drug clearance. Conclusions. While transplant pregnancies are complex, favorable outcomes are achievable through meticulous, multidisciplinary care. Key success factors include the avoidance of teratogens and rigorous monitoring of both blood pressure and drug levels. When managed proactively, most recipients can achieve successful gestational results without compromising long-term graft survival. Continued research remains essential to further refine these high-risk protocols.